UNIT 29.9 Expression and Purification of Haemophilus influenzae Rhomboid Intramembrane Protease GlpG for Structural Studies. Issue 1 (1st April 2014) - Panwar, Pankaj; Lemieux, M. Joanne
Abstract: Rhomboid proteases are membrane‐embedded proteases that cleave peptide bonds of transmembrane proteins. They play a variety of roles in cell signaling events. The rhomboid protease GlpG from Haemophilus influenzae (hiGlpG) is a canonical form of rhomboid protease having six transmembrane segments. In this unit, detailed protocols are presented for optimization of hiGlpG expression using the araBAD promotor system in the pBAD vector. The parameters for optimization include concentration of inducing agent, induction temperature, and time. Optimization of these key factors led to the development of a protocol yielding 1.6 to 2.5 mg/liter protein purified after ion metal affinity chromatography (IMAC). Further purification can include size exclusion chromatography (SEC). Curr. Protoc. Protein Sci . 76:29.9.1‐29.9.25 © 2014 by John Wiley & Sons, Inc.